Improving the Belief-Propagation Convergence of Irregular LDPC Codes Using Column-Weight Based Scheduling - Aslam, Chaudhry Adnan (2015)
In this letter, a novel scheduling scheme for decoding irregular low-density parity-check (LDPC) code, based on the column weight of variable nodes in the code graph, is introduced. In this scheme, the irregular LDPC code is decoded using the shuffled belief-propagation (BP) algorithm by selecting the variable nodes in descending order of their column weight. Via numerical simulation, it is shown that the proposed highto- low column-weight based decoding schedule can noticeably increase the convergence speed at medium to high signal-to-noise ratio (SNR) over AWGN and Rayleigh fading channels without introducing additional complexity or error rate degradation. Furthermore, it is found that the improvement in decoding convergence is proportional to the maximum column-weight in the code graph.